Gas supply reliability analysis of a natural gas pipeline system considering the effects of underground gas storages. (15th October 2019) - Yu, Weichao; Gong, Jing; Song, Shangfei; Huang, Weihe; Li, Yichen; Zhang, Jie; Hong, Bingyuan; Zhang, Ye; Wen, Kai; Duan, Xu
Highlights: A methodology is developed to assess gas supply reliability of a pipeline system. Three aspects of uncertainty and system's hydraulic characteristic are considered. The gas supply strategy of the natural gas pipeline system is proposed. The uncertainty in the gas injection/production capacity is considered. Abstract: Underground gas storage plays a significant role in ensuring gas supply reliability of natural gas pipeline systems. However, the specific hydraulic characteristics of the underground gas storage and the uncertainties in its gas injection/production capacity are generally overlooked when evaluating the gas supply reliability. Therefore, an integrated methodology to assess gas supply reliability of the natural gas pipeline system is developed in this study, and three aspects of uncertainty and hydraulic characteristic of the natural gas pipeline system are both considered. Based on system's gas supply strategy, the amounts of gas supplied by the transmission pipeline system and required by the consumers are calculated firstly. The underground gas storage is then employed to regulate the supply-demand imbalance between the transmission pipeline system and market demand by performing its gas injection/production function. Moreover, the operational reliability of the underground gas storage is evaluated to determine whether it is able to complete the specified gas injection/production task. Then, the total daily amount of gas supplied to the consumers, is obtained, and two indicators proposed to quantify the gas supply reliability are then calculated. Finally, the expected gas supply reliability is assessed based on a large number of Monte Carlo trials. Moreover, the methodology is applied to a simplified gas pipeline system to confirm its feasibility, and system's ability to satisfy the consumers demand is evaluated, and the weakest consumer node is identified. Furthermore, the gas supply reliability is overestimated without considering the uncertainties in the underground gas storage's gas injection/production capacity.